(untitled) (Homiletic, 2022)
The trauma experienced by marginalized communities often results from violence operating on many levels, not the least of which is economic. Victims of economic oppression and exploitation cry out to the church for a balm. That homiletical balm must call the church back to its rightful pursuit of liberation and render its complicity in economic oppression visible. Such a homiletical effort can be anchored in a theology emerging from the Lazarus narrative in John. A re-reading of that text offers a liberative homiletic that speaks to this moment in American culture.